(untitled) (Nexo Revista Científica, 2020)
The article describes the role of Russia in the global gas industry, on the basis of the analysis of the factual data cited, conclusions are drawn about the provision of the economy with the considered minerals, the main problems in managing the supply chains of natural gas and liquefied natural gas are formulated, and innovative ways to solve them are proposed. Based on the fuzzy modeling method, it was shown that the maximum amount of budget revenues from the export duty of Russian natural gas from the main gas-bearing regions can almost double. At the same time, the minimum volume in the same case remains virtually unchanged, remaining within 10%. The use of fuzzy modeling in innovation management in the supply chains of Russian natural gas is caused by high volatility in the global commodity markets, both for the underlying asset (in this case, natural gas) and for derivative financial instruments (derivatives). Based on the simplex optimization method, innovation management schemes have been developed in the supply chains of Russian natural gas, taking into account the regional structure of its production. The differences in the economic efficiency of the export duty for the Russian budget between the supply of pipeline natural gas and liquefied natural gas are shown. The author’s methods presented in the article can be used as additional innovative tools for making strategic and operational management decisions by industry leaders and public authorities.